Post-traumatic scalp lipoma: A case report - Zilefac Brian Ngokwe; Kharim-Charles Lyonga; Achumbom Haggai Akumbom; Karl Njuwa Fai (Oral and Maxillofacial Surgery Cases, 2023)
Lipomas are a type of mesenchymal neoplasm most commonly occurring in the subcutaneous compartment and can be distributed throughout the body. These tumors are most commonly found in the upper part of the body. Their growth is slow and are usually small, weighing only a few grams. A link has been established between soft tissue trauma and the development of lipomas, which have been dubbed, posttraumatic lipomas. We hereby present a case of a solitary slowly evolving fronto-parietal scalp lipoma following a local blunt trauma.